2019
DOI: 10.1111/jcmm.14918
|View full text |Cite
|
Sign up to set email alerts
|

An outcome model for human bladder cancer: A comprehensive study based on weighted gene co‐expression network analysis

Abstract: The precision evaluation of prognosis is crucial for clinical treatment decision of bladder cancer (BCa). Therefore, establishing an effective prognostic model for BCa has significant clinical implications. We performed WGCNA and DEG screening to initially identify the candidate genes. The candidate genes were applied to construct a LASSO Cox regression analysis model. The effectiveness and accuracy of the prognostic model were tested by internal/external validation and pan-cancer validation and time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In this study, we find that the model variables were screened by LASSO Cox regression has better accuracy and resolution than the model variables were screened by Forward Stepwise Cox regression. Number of studies have shown that it plays an important role in cancer research: especially in lung adenocarcinoma [ 18 ]; bladder cancer [ 19 ]; gastric cancer [ 20 ]; and pancreatic cancer [ 21 ]. Meanwhile, Liu et al applied LASSO Cox regression to the establishment of a prognostic model for hepatocellular carcinoma [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we find that the model variables were screened by LASSO Cox regression has better accuracy and resolution than the model variables were screened by Forward Stepwise Cox regression. Number of studies have shown that it plays an important role in cancer research: especially in lung adenocarcinoma [ 18 ]; bladder cancer [ 19 ]; gastric cancer [ 20 ]; and pancreatic cancer [ 21 ]. Meanwhile, Liu et al applied LASSO Cox regression to the establishment of a prognostic model for hepatocellular carcinoma [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…LASSO Cox regression analysis constructs a penalty function to obtain a more refined model. And a number of studies have shown that it plays an important role in cancer research: Li et al applied LASSO Cox regression to the establishment of a prognostic model for lung adenocarcinoma [ 18 ]; Xiong et al establishment of an outcome model for bladder cancer [ 19 ]; Jiang et al establishment of a prognostic model gastric cancer [ 20 ]; Wu et al establishment of a prognostic model pancreatic cancer [ 21 ]. Meanwhile, Liu et al applied LASSO Cox regression to the establishment of a prognostic model for hepatocellular carcinoma [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The forest was used to show the P-values , HR and 95% confidence interval (CI) of each variable through 'forestplot' R package. A nomogram was developed based on the results of multivariate Cox proportional hazards analysis to predict the 1-year, 2-year, and 3-year overall recurrence 43 . The nomogram provided a graphical representation of the factors, which can be used to calculate the risk of recurrence for an individual patient by the points associated with each risk factor through 'rms' R package 44 .…”
Section: Methodsmentioning
confidence: 99%
“…At present, it has been widely used to compare differentially expressed genes (DEGs) and help investigating the interactions among genes in different modules [24]. Besides, it is also used to identify rules for predicting survival of patients by investigating the relationship between clinical traits and tissue microarray data [25].…”
Section: Introductionmentioning
confidence: 99%